Quality of life, health and social costs of patients with spinal cord injury: A systematic review. (20th October 2021) - Diop, M; Epstein, D; Gaggero, A
Abstract: Objective: To systematically reviews the costs, resource uses, clinical complication and quality of life among patients with spinal cord injury. Methods: A systematic review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement was conducted through Scopus, PubMed and Embase databases. Results: A total of 52 studies were eligible for inclusion. The estimated lifetime economic burden per individual with SCI ranges from $1.5 million to $3.0 million. Among studies which reported clinical outcomes, the mortality rates were estimated less than 4%, the most medical complication reported are spasticity, pain, pressures score and neurological deteriorations. Overall health status is negatively associated with QoL. People with a higher severity the of injury, a longer duration of injury, ambulatory mode, and with depression are more likely to report score low values of QoL. Employment and salary are consistently positively associated with better QoL. Age is negatively correlated with QoL. Conclusions: Although spinal cord injury is related with high costs, no studies were found with detailed resources use. Also, A variety of instrument were used to examine how different factors have a role in predicting quality of life in spinal cord injury population. However, it is important to consider that differences found in those studies may at least be part in function of the instruments used. Therefore, standardized instruments should be used as part of these process. Key messages: Paraplegia or the severity of SCI impact negatively quality of life and positively on healthcare and social costs. Promoting the employment of subjects with SCI generates a positive impact on their quality of life.